2021
DOI: 10.21147/j.issn.1000-9604.2021.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Current status of lymph node dissection in gastric cancer

Abstract: Gastrectomy with lymph node (LN) dissection has been regarded as the standard surgery for gastric cancer (GC), however, the rational extent of lymphadenectomy remains controversial. Though gastrectomy with extended lymphadenectomy beyond D2 is classified as a non-standard gastrectomy, its clinical significance has been evaluated in many studies. Although hard evidence is lacking, D2 plus superior mesenteric vein (No. 14v) LN dissection is recommended when harbor metastasis to No. 6 nodes is suspected in the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…D2 radical resection has been accepted as the only effective treatment for resectable GC [ 9 10 11 ]. However, a large proportion of patients experience recurrence and metastasis within 2 years of D2 radical resection, resulting in poor prognosis, with a 5-year survival rate of <50% [ 12 13 14 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…D2 radical resection has been accepted as the only effective treatment for resectable GC [ 9 10 11 ]. However, a large proportion of patients experience recurrence and metastasis within 2 years of D2 radical resection, resulting in poor prognosis, with a 5-year survival rate of <50% [ 12 13 14 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the most important independent prognostic factor for GC, [1–3] great emphasis was put on the LN involvement assessing, and currently, two N-stage systems were most recognized: the Japanese Classification of Gastric Carcinoma (JCGC, 13th edition) N-classification system and Union International Cancer Control (UICC-TNM, 8th edition) N-staging system. JCGC N-classification system is based on the anatomic location-based involved node stations, whereas the UICC-TNM N-staging system is based on the number of MLNs [2,22,23] .…”
Section: Discussionmentioning
confidence: 99%
“…As we knew, postoperative adjuvant chemotherapy based on histological and biological characteristics to determine tailored treatment for specific subgroups could further improve the prognosis of GC patients. [38] Although LN metastasis has been demonstrated to be the strongest predictor of disease recurrence for GC [1][2][3] and even might be the active hubs for systemic tumor cell spread. [8,9] At the same time, it has been demonstrated that more intensive adjuvant chemotherapy was safe and could significantly improve prognosis for the subgroup GC patients with an indication for intense adjuvant chemotherapy in serious trials in Japan, including the Adjuvant Chemotherapy Trial of S-1 for Gastric Cancer study, [39] the Japan Clinical Oncology Group 1104 trial, [40] and the Japan Clinical Cancer Research Organization GC-07 trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations